Nanotechnology in packaging of food and drugs - Badiei M.; Asim N.; Samsudin N.A.; Amin N.; Sopian K. (Elsevier, 2023)
The packaging industry needs potential materials to ensure the safety and prolong the shelf life of food and drugs. Polymer nanocomposites have been introduced as promising materials for the packaging of foods and drugs because of their customizable properties. This chapter highlights the current nanotechnology developments being exploited for sustainable packaging. Moreover, the application of nanocellulose and its derivatives in advanced packaging materials is reviewed. Relevant applications include the enhancement of the barrier and antimicrobial properties of packaging materials. Moreover, the nanomaterials that have been used for sensing and detecting pathogens and gasses as deteriorating agents of foods and drugs are reviewed in this study. 2022 Elsevier Inc. All rights reserved.